Marginalisasi Perempuan Dalam Novel Nyutrayu Karya Joko Gesang Santoso - Zahrotul Mawaddah; Harjito Harjito; Ika Septiana (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
The purpose of this research is to describe the marginalization of women in the novel "Nyutrayu" by Joko Gesang Santoso. The research method used is qualitative descriptive method. The presentation technique of the research results uses the note-taking technique. The results show various forms of women's marginalization such as women becoming victims of patriarchal power where men hold more authority, the belief that women should not surpass men, being ostracized due to physical differences such as having blue eyes which creates the perception that blue-eyed individuals are foreigners and not indigenous, the attitude of demeaning women leading to their social exclusion, and the impoverishment causing women to lose their belongings. Female characters experiencing marginalization in the novel "Nyutrayu" include Aran, Sumi, and Lara, which can be seen through their behavior, dialogues, portrayal through other characters, thoughts, and dialogues among characters. These characters experience marginalization, leading them to choose a life of silence, gouging out their own eyes to avoid seeing others' past and future, resigning themselves to being objectified by men to satisfy male sexuality, and allowing themselves to be marginalized by living on the outskirts of a village far from the community.